A COFs / nitrogen vacancy-based g-C3N4 material with organic functional groups, its preparation method, and its application.

CN118162109BActive Publication Date: 2026-10-23HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410270465.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2026-10-23
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

[0006]本发明旨在解决水体中氯酚类化合物难吸附、难处理等技术问题

Benefits of technology

[0073]1、传统体相石墨烯碳化氮为片层结构,无孔径,比表面积仅为20~30m2/g。本材料具有介孔(孔径3.2~3.3nm)和巨大的比表面积(≥200m2/g),有利于入射光在材料内部的反射和衍射,同时为氯酚类化合物提供了大量的吸附位点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004734004620000131
    Figure BDA0004734004620000131
  • Figure HDA0004734004630000011
    Figure HDA0004734004630000011
  • Figure HDA0004734004630000012
    Figure HDA0004734004630000012
Patent Text Reader

Abstract

The present application belongs to the technical field of environmental analysis and water treatment, and particularly relates to an organic functional group COFs / nitrogen vacancy g-C3N4 material and a preparation method and application thereof. The present application uses melamine as a precursor, potassium hydroxide as an etchant, and obtains graphite phase carbon nitride containing nitrogen vacancies by one-step calcination under a nitrogen atmosphere; then, using organic functional group organic compounds, 4,4',4''-(1,3,5-triazinane-1,3,5-triyl) triphenylamine and graphite phase carbon nitride containing nitrogen vacancies as raw materials, 1,2-dichlorobenzene and n-butanol as solvents, and acetic acid as a catalyst, an organic functional group COFs / nitrogen vacancy g-C3N4 material is prepared by a solvothermal method. The material of the present application can not only be used as a solid phase extraction adsorbent for detecting chlorophenol compounds in water, but also can be used as a photocatalyst for photocatalytic degradation of chlorophenol compounds in water, solving the technical problems of difficult adsorption and treatment of chlorophenol compounds in water, high energy consumption of traditional photocatalysts, high recombination rate of photo-generated carriers, and low degradation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of environmental analysis and water treatment technology, and more specifically, to a g-C3N4 material with organic functional groups COFs / nitrogen vacancies, its preparation method, and its application. Background Technology

[0002] Chlorophenols are representative organic pollutants, abundant in pharmaceutical, textile, and coal wastewater. These toxic substances can spread through environmental media, ultimately harming human health. Traditional water treatment processes, such as adsorption and biological treatment, are either costly or inefficient at removing chlorophenols. Therefore, it is necessary to explore new treatment technologies.

[0003] Photocatalysis is a highly efficient and environmentally friendly method for degrading chlorophenols. Under illumination, photocatalysts absorb photons with sufficient energy, generating electron-hole pairs. These photogenerated carriers then diffuse and migrate to the catalytically active sites to initiate redox reactions, leading to the complete mineralization of organic pollutants.

[0004] Covalent organic monomers are crystalline porous organic polymers integrated through covalent bonds, known as covalent organic frameworks (COFs). COFs possess advantages such as low density, large specific surface area, and tunable pore size and structure, showing great potential for improving photocatalytic performance. Different organic monomers can synthesize different COFs, and current research mainly focuses on synthesizing novel COFs using different types of organic monomers, while research on the influence of different functional groups on the catalytic performance of COF materials is scarce.

[0005] Compared to COFs, graphitized carbon nitride (g-C3N4) is a more commonly used photocatalyst, exhibiting visible light response and high physicochemical stability. However, its small specific surface area, insufficient visible light absorbance, and high electron-hole recombination rate significantly limit its application. Inducing nitrogen vacancies can modify the electronic structure and reduce the recombination probability of photogenerated carriers. Meanwhile, heterostructure construction is also one of the most effective modification methods; the presence of a second material can significantly optimize the performance of a single catalyst. Summary of the Invention

[0006] This invention aims to solve the technical problems of the difficult adsorption and treatment of chlorophenol compounds in water. Traditional photocatalysts such as titanium dioxide require ultraviolet light sources, resulting in high energy consumption; bulk graphitic nitrogen carbide can be used in the visible light region, but its high photogenerated carrier recombination rate leads to low degradation efficiency for chlorophenol pollutants. This invention provides an experimental method for the analysis and removal of chlorophenol compounds in water using a vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 composite material. This invention synthesizes two COFs with different functional groups (CHO-R, R=C=C or OH) using 4,4',4”-(1,3,5-triazine-2,4,6-triyl)triphenylamine and terephthalaldehyde as raw materials. These COFs are then combined with nitrogen-vacancy-rich g-C3N4 to construct heterojunctions. Finally, the vinyl or hydroxyl COFs combined with nitrogen-vacancy-rich g-C3N4 are used to analyze and remove chlorophenolic compounds from water. This invention utilizes vinyl or hydroxyl covalent organic framework materials / nitrogen-vacancy graphitic carbon nitride composite materials for the analysis and removal of chlorophenolic compounds from water.

[0007] To achieve the above objectives, a first aspect of the present invention provides a method for preparing a g-C3N4 material with organic functional groups COFs / nitrogen vacancies, comprising the following steps:

[0008] S1. Preparation of graphitic carbon nitride containing nitrogen vacancies: Melamine and etching agent are mixed and calcined at high temperature under nitrogen atmosphere to obtain graphitic carbon nitride containing nitrogen vacancies.

[0009] S2. Preparation of organic functional group COFs / nitrogen vacancy graphitic carbon nitride: The graphitic carbon nitride containing nitrogen vacancies, organic compounds containing organic functional groups and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine were mixed, organic solvent and catalyst were added, and the mixture was ultrasonically dispersed. After freezing, vacuum and thawing were repeated 2 to 4 times. The mixture was then sealed and stored at high temperature. After cooling, the solid precipitate was centrifuged and washed with anhydrous N,N-dimethylacetamide and tetrahydrofuran until the supernatant was colorless. The mixture was then washed with acetone and vacuum dried to obtain g-C3N4 material with organic functional group COFs / nitrogen vacancy.

[0010] The mass ratio of the nitrogen-vacant graphitic carbon nitride, the organic compound containing an organic functional group, and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine is (1.8-2.2):1:(1-1.5); the organic compound containing an organic functional group is 2,5-divinyl terephthalaldehyde or 2,5-dihydroxy terephthalaldehyde.

[0011] Preferably, in step S1, the etching agent is potassium hydroxide, and the mass ratio of melamine to potassium hydroxide is (20-40):1.

[0012] Preferably, in step S1, the high-temperature calcination conditions are: heating to 400-600°C at a rate of 8-12°C / min for 3.5-4.5 hours.

[0013] Preferably, in step S2, the organic solvent is one or more of 1,2-dichlorobenzene and n-butanol, and the mass-to-volume ratio (mg / mL) of the graphitic carbon nitride containing nitrogen vacancies to the organic solvent is (30-50):1; the catalyst is an acetic acid solution, the mass-to-volume ratio (mg / mL) of the graphitic carbon nitride containing nitrogen vacancies to the acetic acid solution is (380-420):1, and the concentration of the acetic acid solution is 6 mol·L⁻¹. -1 .

[0014] Preferably, the ultrasonic dispersion conditions are: frequency 60-100Hz, time 20-25min; freezing conditions are: freezing in liquid nitrogen for 2-3min; vacuum conditions are: pressure not exceeding 85Pa, time 2-3min; thawing conditions are: thawing at room temperature for 2-3min; high-temperature sealed storage time is 2-4 days, temperature is 100-120℃; centrifugation conditions are: speed 8000-10000rpm, time 8-10min.

[0015] In a second aspect, the present invention provides a g-C3N4 material with organic functional groups COFs / nitrogen vacancies prepared by the above-described preparation method.

[0016] A third aspect of the present invention provides an application of the g-C3N4 material with organic functional group COFs / nitrogen vacancies prepared by the above-described preparation method, characterized in that:

[0017] (1) Used for the detection of chlorophenol compounds in water; and / or

[0018] (2) Used for photocatalytic degradation of chlorophenol compounds in water;

[0019] The chlorophenolic compounds include one or more of 4-chlorophenol, 2,4-dichlorophenol, and 2,4,6-trichlorophenol.

[0020] Preferably, the method for detecting chlorophenol compounds in a water sample includes the following steps:

[0021] Sa1. Preparation of the sample solution to be tested: Using organic functional group COFs / nitrogen vacancy g-C3N4 as solid phase extraction adsorbent, chlorophenol compounds in water sample are extracted, organic functional group COFs / nitrogen vacancy g-C3N4 after extraction is eluted, and the eluent is concentrated to obtain the sample solution to be tested.

[0022] Sa2. Detection of chlorophenolic compounds: The sample solution to be tested was separated and detected by GC-ECD, and a standard curve was plotted using the external standard method to calculate the concentration of chlorophenolic compounds in the sample solution.

[0023] The GC-ECD was performed using an Agilent 7890A gas chromatograph equipped with an autosampler. The chromatographic column was an Agilent HP-5 capillary column, 30m × 0.32mm long and 0.25μm in diameter. High-purity nitrogen was used as the carrier gas at a flow rate of 1.0mL / min. The initial temperature of the column oven was 40℃ and held for 3min, followed by a temperature increase to 300℃ at a rate of 10℃ / min and held for 5min. The injection port temperature was 260℃. The split injection mode was 1:5, and the injection volume was 1μL.

[0024] Preferably, the method for photocatalytic degradation of chlorophenol compounds in a water sample includes the following steps: adding an aqueous solution containing chlorophenol to g-C3N4 with organic functional groups COFs / nitrogen vacancies, stirring magnetically in the dark until the g-C3N4 with organic functional groups COFs / nitrogen vacancies is uniformly dispersed in the aqueous solution containing chlorophenol to obtain a suspension, irradiating the suspension with visible light for 200-300 min at a temperature of 23-25°C, centrifuging to separate the liquid portion, and obtaining the water sample after degradation of chlorophenol compounds;

[0025] The mass-to-volume ratio (g / L) of the organic functional group COFs / nitrogen vacancy g-C3N4 and the aqueous solution of the chlorophenolic compound is 1:(2-3), and the concentration of the chlorophenolic compound in the aqueous solution is 1-2 mg / L; the magnetic stirring conditions are 80-120 rpm for 25-35 min; and the centrifugation conditions are 8000-10000 rpm for 8-10 min.

[0026] Preferably, the water sample includes one or more of surface water, groundwater, tap water, or filtered domestic sewage.

[0027] Detailed overview of the invention

[0028] A method for preparing an organic functional group COFs / nitrogen vacancy g-C3N4 material includes the following steps:

[0029] S1. Preparation of g-C3N4 containing nitrogen vacancies: Using melamine as a precursor and potassium hydroxide as an etchant, g-C3N4 containing nitrogen vacancies was obtained by one-step calcination under a nitrogen atmosphere.

[0030] S2. Preparation of COFs / nitrogen vacancy g-C3N4 material with organic functional groups: Using organic compounds containing organic functional groups, 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine and graphitic carbon nitride containing nitrogen vacancies as raw materials, 1,2-dichlorobenzene and n-butanol as solvents, and acetic acid as catalyst, g-C3N4 material with COFs / nitrogen vacancies was prepared by solvothermal method.

[0031] This invention discloses experimental methods for the analysis and removal of chlorophenolic compounds from water using g-C3N4 with nitrogen vacancies and two types of vinyl or hydroxyl COFs complexes. The purpose of this invention is to solve the technical problems of existing methods, such as the difficulty in adsorbing and treating chlorophenolic compounds, and the high energy consumption, high recombination rate of photogenerated carriers, and low degradation efficiency of traditional photocatalysts. This invention uses a tube furnace high-temperature calcination method to prepare graphitic carbon nitride containing nitrogen vacancies, and then uses a solvothermal method to prepare a covalent organic framework / nitrogen-vacancy graphitic carbon nitride composite material, which is then applied to the analysis and removal of chlorophenolic compounds from water. The material obtained by this invention is hydrophilic, easily dispersed in water, inexpensive, stable, and reusable.

[0032] In some embodiments of the present invention, the material prepared by the present invention is a vinyl COFs / nitrogen vacancy g-C3N4 material, comprising the following steps:

[0033] Sa1. Preparation of g-C3N4 containing nitrogen vacancies: Using melamine as a precursor and potassium hydroxide as an etchant, g-C3N4 containing nitrogen vacancies was obtained by a one-step calcination method under a nitrogen atmosphere. The specific process is as follows:

[0034] A mixture of melamine and potassium hydroxide was added to a sample boat in a tube furnace. The tube furnace was then shut off, and nitrogen gas was introduced into the furnace at a rate of 20 mL / min. After 30 min, the temperature of the tube furnace was increased to 550 °C at a rate of 10 °C / min. After the reaction was complete, the resulting pale yellow solid was ground into powder using an agate mortar and pestle, which is the g-C3N4 material containing nitrogen vacancies.

[0035] In the preferred embodiment, the mass ratio of melamine to potassium hydroxide is 30:1.

[0036] In the preferred manner, the calcination reaction time is 4 to 5 hours.

[0037] Sa2, Vinyl COFs / Nitrogen Vacancy g-C3N4: Using 2,5-divinylterephthalaldehyde, 4,4',4”-(1,3,5-triazinane-1,3,5-triyl)triphenylamine, and nitrogen-vacancy-containing g-C3N4 obtained in step Sa1 as raw materials, 1,2-dichlorobenzene and n-butanol as solvents, and acetic acid as catalyst, a solvothermal method was used to prepare vinyl COFs / nitrogen vacancy g-C3N4 materials. The specific process is as follows:

[0038] The mixture of g-C3N4 containing nitrogen vacancies, 2,5-divinylterephthalaldehyde, and 4,4',4”-(1,3,5-triazinane-1,3,5-triyl)triphenylamine prepared in step Sa1 was added to a high-temperature resistant glass tube (outer diameter 9.8 mm, inner diameter 6 mm), followed by the addition of 1,2-dichlorobenzene, n-butanol, and acetic acid. After ultrasonic dispersion for 20–25 min (frequency 80 kHz), the mixture was placed in liquid nitrogen for 2–3 min, evacuated for 2–3 min (85 Pa), and thawed at room temperature for 2–3 min. The freezing-vacuum-thawing process was repeated three times. Finally, the heat-resistant glass tube was sealed with a flame at 1300°C and stored in an oven at 120°C for 3 days. After cooling to room temperature, the solid precipitate was collected by high-speed centrifugation (9000 rpm, 8–10 min) and washed 5–8 times with anhydrous N,N-dimethylacetamide and tetrahydrofuran until the supernatant became colorless. The covalent organic framework of the product was washed with acetone and dried under vacuum overnight (50 Pa, 60°C) to obtain vinyl COFs / nitrogen vacancy g-C3N4.

[0039] In the preferred embodiment, the mass ratio of g-C3N4 containing nitrogen vacancies, 2,5-divinyl terephthalaldehyde, and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine is 16:8:11.

[0040] In the preferred embodiment, the volume ratio of 1,2-dichlorobenzene, n-butanol, and acetic acid is 5:5:1.

[0041] In the preferred configuration, the concentration of acetic acid is 6 mol·L⁻¹. -1 .

[0042] In some embodiments of the present invention, the prepared material is a hydroxyl COFs / nitrogen vacancy g-C3N4 material, comprising the following steps:

[0043] Sb1. Preparation of g-C3N4 containing nitrogen vacancies: Using melamine as a precursor and potassium hydroxide as an etchant, g-C3N4 containing nitrogen vacancies was obtained by a one-step calcination method under a nitrogen atmosphere. The specific process is as follows:

[0044] A mixture of melamine and potassium hydroxide was added to a sample boat in a tube furnace. The tube furnace was then shut off, and nitrogen gas was introduced into the furnace at a rate of 20 mL / min. After 30 min, the temperature of the tube furnace was increased to 550 °C at a rate of 10 °C / min. After the reaction was complete, the resulting pale yellow solid was ground into powder using an agate mortar and pestle to obtain g-C3N4 material containing nitrogen vacancies.

[0045] In the preferred embodiment, the mass ratio of melamine to potassium hydroxide is 30:1.

[0046] In the preferred manner, the calcination reaction time is 4 to 5 hours.

[0047] Sb2, Hydroxyl COFs / Nitrogen Vacancy g-C3N4 Material: Using 2,5-dihydroxyterephthalaldehyde, 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine, and nitrogen-vacancy-containing g-C3N4 obtained in step Sb1 as raw materials, 1,2-dichlorobenzene and n-butanol as solvents, and acetic acid as a catalyst, a solvothermal method was employed to prepare hydroxyl COFs / nitrogen vacancy g-C3N4. The specific process is as follows:

[0048] The mixture of g-C3N4 containing nitrogen vacancies, 2,5-dihydroxyterephthalaldehyde (40 mg), and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine (55 mg) prepared in step Sb1 was added to a high-temperature resistant glass tube (outer diameter 9.8 mm, inner diameter 6 mm), followed by the addition of 1,2-dichlorobenzene (1 mL), n-butanol (1 mL), and acetic acid (0.2 mL, 6 mol·L⁻¹). -1 After ultrasonic dispersion for 20–25 min (frequency 80 kHz), the mixture was frozen in liquid nitrogen for 2–3 min, evacuated for 2–3 min, and thawed at room temperature for 2–3 min. This freezing-vacuum-thawing process was repeated three times. Finally, the heat-resistant glass tube was sealed with a flame at 1300 °C and stored in an oven at 120 °C for 3 days. After cooling to room temperature, the solid precipitate was collected by high-speed centrifugation (9000 rpm, 8–10 min) and washed 5–8 times with anhydrous N,N-dimethylacetamide and tetrahydrofuran until the supernatant became colorless. The covalent organic framework of the product was washed with acetone and dried under vacuum overnight (50 Pa, 60 °C) to obtain vinyl COFs / nitrogen vacancy g-C3N4.

[0049] In some embodiments of the present invention, the mass ratio of g-C3N4 containing nitrogen vacancies, 2,5-dihydroxyterephthalaldehyde, and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine is 16:8:11.

[0050] In some embodiments of the present invention, the volume ratio of 1,2-dichlorobenzene, n-butanol, and acetic acid is 5:5:1.

[0051] In some embodiments of the present invention, the concentration of acetic acid is 6 mol·L⁻¹. -1 .

[0052] The specific procedure for analyzing chlorophenolic compounds in water using the vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 prepared above is as follows:

[0053] Vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 material (solid-phase adsorbent) was added to a 100 mL double-layer quartz reactor, followed by water or an aqueous solution containing chlorophenols. Under dark conditions, the material was uniformly dispersed in the solution by magnetic stirring (100 rpm) for 30 min to achieve adsorption-desorption equilibrium of the chlorophenols. After the reaction was complete, the material was separated from the liquid using a high-speed centrifuge (9000 rpm, 8 min). The material was washed with eluent and sonicated for 2 min (80 kHz) to elute trace amounts of the analyte adsorbed on its surface. This elution was repeated 2–3 times, followed by high-speed centrifugation (9000 rpm, 8–10 min). The eluents were collected and combined. The collected eluent was dried under nitrogen at 45 °C, and 1 mL of n-hexane was added for reconstitution to obtain the test sample solution. Gas chromatography with an electron capture detector (GC-ECD) was used to analyze and detect the three chlorophenols in the test sample solution.

[0054] The GC-ECD instrument was an Agilent 7890A, equipped with an autosampler. The column was an Agilent HP-5 capillary column (30m × 0.32mm, 0.25μm). High-purity nitrogen was used as the carrier gas at a flow rate of 1.0 mL / min. The column oven temperature was initially set at 40℃ and held for 3 min, then increased to 300℃ at a rate of 10℃ / min and held for 5 min. The injection port temperature was 260℃; injection was performed in splitless mode; the injection volume was 1 μL; the detector temperature was 300℃; and nitrogen was used as the make-up gas at a flow rate of 3.0 mL / min.

[0055] The positive samples, i.e. water samples containing chlorophenol compounds, were retested using gas chromatography-tandem triple quadrupole mass spectrometry (GC-QQQ).

[0056] The GC-QQQ instrument was an Agilent 7890A-7000B equipped with an autosampler. The chromatographic column was an Agilent HP-5m capillary column (30m long × 0.25mm, 0.25μm). High-purity helium was used as the carrier gas at a flow rate of 1.0mL / min. The initial temperature of the column oven was 40℃ and held for 3min, then increased to 300℃ at a rate of 10℃ / min and held for 5min. The injection port temperature was 260℃; the injection mode was splitless; the injection volume was 1μL; the scanning mode was multiple reaction monitoring (MRM). For relevant parameters, please refer to the references (International Journal of Environmental Analytical Chemistry, 2018, 98(5):413–428 and Science of the Total Environment, 2018, 618:70–79).

[0057] In some embodiments of the present invention, the mass ratio of solid adsorbent to water sample is 20 mg: 50 mL.

[0058] In some embodiments of the present invention, the chlorophenolic compounds include one or a mixture of several of 4-chlorophenol, 2,4-dichlorophenol, and 2,4,6-trichlorophenol.

[0059] In some embodiments of the present invention, the eluent is acetonitrile.

[0060] In some embodiments of the present invention, the mass ratio of solid-phase adsorbent to eluent is 20 mg: 2 mL.

[0061] The specific operation process of using the vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 prepared above to remove chlorophenol compounds from water is as follows:

[0062] Vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 (photocatalyst) was added to a 100 mL double-layer quartz reactor, followed by the addition of an aqueous solution containing chlorophenol compounds. Under dark conditions, the material was uniformly dispersed in the solution by magnetic stirring (100 rpm) for 30 min to achieve adsorption-desorption equilibrium of chlorophenol organic compounds. The suspension was then placed in a 300 W visible light irradiation area for 200–300 min. The material was separated from the aqueous phase using a high-speed centrifuge (9000 rpm, 8 min). Eluent was added for washing, followed by sonication for 2–3 min (80 kHz) to elute trace analytes adsorbed on the surface. This elution was repeated 2–3 times, followed by high-speed centrifugation (9000 rpm, 8–10 min). The eluents were collected and combined. The collected eluent was dried under nitrogen at 45 °C, and 1 mL of n-hexane was added for reconstitution to obtain the test sample solution. GC-ECD was used to analyze and quantify the chlorophenolic compounds in the test sample solution.

[0063] The GC-ECD instrument was an Agilent 7890A, equipped with an autosampler. The column was an Agilent HP-5 capillary column (30m × 0.32mm, 0.25μm). High-purity nitrogen was used as the carrier gas at a flow rate of 1.0 mL / min. The column oven temperature was initially set at 40℃ and held for 3 min, then increased to 300℃ at a rate of 10℃ / min and held for 5 min. The injection port temperature was 260℃; injection was performed in splitless mode; the injection volume was 1 μL; the detector temperature was 300℃; and nitrogen was used as the make-up gas at a flow rate of 3.0 mL / min.

[0064] In the aqueous phase from which the catalyst was separated, acetonitrile was added as the extractant, and the mixture was homogenized and shaken for 2 min. Sodium chloride was then added, and after shaking to dissolve and reach equilibrium, the mixture was allowed to stand and separate into layers. The organic phase was then removed. The extractant was added again, and the extraction was repeated once more. The organic phases were combined and dried at 45°C by nitrogen blowing or rotary evaporation. 1 mL of n-hexane was added for reconstitution, yielding the aqueous extract. GC-ECD was used to analyze and quantify the chlorophenol compounds in the extract. The chlorophenol contents of the sample solution and the aqueous extract were summed, and then divided by the initial chlorophenol content in the water to calculate the photocatalytic efficiency of vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 for chlorophenol compounds in the water. The calculation formula is as follows:

[0065] Degradation rate (%) = [(C0 – C t ) / C0]×100%

[0066] Where C0 refers to the initial concentration of chlorophenol in the water, C t This refers to the concentration of chlorophenol in water after a period of irradiation.

[0067] In the preferred embodiment, both the eluent and the extractant are acetonitrile.

[0068] In the preferred embodiment, the mass ratio of photocatalyst to water sample is 20 mg: 50 mL;

[0069] In the preferred embodiment, the mass ratio of photocatalyst to eluent is 20 mg: 2 mL;

[0070] In the preferred embodiment, the mass ratio of aqueous phase, primary extractant, and sodium chloride is 5:5:1.

[0071] In the preferred embodiment, the mass ratio of the primary extractant to the secondary extractant is 5:3.

[0072] The beneficial effects of this invention are:

[0073] 1. Traditional bulk graphene nitrogen carbide has a layered structure with no pores and a specific surface area of ​​only 20-30 m². 2 / g. This material has mesoporous structure (pore size 3.2–3.3 nm) and a large specific surface area (≥200 m² / g). 2 / g), which is beneficial for the reflection and diffraction of incident light inside the material, and at the same time provides a large number of adsorption sites for chlorophenol compounds.

[0074] 2. The main framework of this material contains abundant benzene ring structures, and it utilizes π-π conjugation to adsorb chlorophenols. This is beneficial for the selective adsorption of chlorophenol pollutants, and rapid elution is achieved by breaking van der Waals forces. This avoids the problems of difficult elution and difficult regeneration of target substances after adsorption by traditional carbon materials.

[0075] 3. This material possesses abundant nitrogen vacancies and heterojunctions, which facilitate electron transfer of photogenerated carriers and enhance its visible light photocatalytic performance. Under 300W xenon lamp irradiation for 200 min, the degradation efficiency of bulk graphitic nitrogen carbide for 2,4,6-trichlorophenol is less than 30%, but the degradation rate of vinyl COFs / nitrogen vacancy g-C3N4 is as high as over 90%.

[0076] 4. This material utilizes the synergistic effect of different functional groups and nitrogen vacancies to enhance the transfer of photogenerated electrons and photocatalytic performance. The degradation rate k of 4-chlorophenol in water by hydroxyl COFs, vinyl COFs, and nitrogen vacancy g-C3N4 is 0.013 min. -1 0.016min -1 and 0.004min -1 The degradation rate of 4-chlorophenol was significantly increased by 0.022 min for the combined hydroxyl COFs / nitrogen vacancy g-C3N4 and vinyl COFs / nitrogen vacancy g-C3N4, with k = 0.022 min. -1 and 0.031min -1 . Attached Figure Description

[0077] Figure 1 This is a schematic diagram of transmission electron microscopy characterization of hydroxyl COFs / nitrogen vacancy g-C3N4 material (left) and vinyl COFs / nitrogen vacancy g-C3N4 material (right);

[0078] Figure 2 This is the GC-QQQ total ion chromatogram of chlorophenols;

[0079] Figure 3 This is a schematic diagram illustrating the degradation of chlorophenolic compounds in water by hydroxyl COFs / nitrogen vacancy g-C3N4 and vinyl COFs / nitrogen vacancy g-C3N4. Detailed Implementation

[0080] The embodiments of the present invention will now be clearly and completely described in conjunction with examples. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0081] The pharmaceuticals and reagents used in this invention are mostly analytical grade and were purchased from Aladdin Reagent Company. The three chlorophenol standards have a purity greater than 99% and were purchased from the Institute of Environmental Standards and Technology (INES). The light source is a xenon lamp from Pofil Technology equipped with a 420nm filter. Other equipment has no special requirements. Furthermore, unless specific conditions are specified in the examples, conventional conditions or conditions recommended by the manufacturer should be followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products. Those skilled in the art will understand that the examples describe the invention by way of illustration and are not intended to limit the scope of protection claimed by the invention. All disclosures and other references mentioned herein are incorporated herein by reference in their entirety.

[0082] Unless otherwise specified, the experiments and methods described in the embodiments are performed in accordance with conventional methods well known in the art and described in various references.

[0083] A method for preparing vinyl or hydroxyl covalent organic framework materials / nitrogen-vacancy graphitic carbon nitride, the method comprising the following steps:

[0084] S1. Preparation of graphitic carbon nitride containing nitrogen vacancies: Using melamine as a precursor and potassium hydroxide as an etchant, graphitic carbon nitride containing nitrogen vacancies was obtained by one-step calcination under a nitrogen atmosphere.

[0085] S2, Vinyl covalent organic framework material / nitrogen vacancy graphitic carbon nitride: Using 2,5-divinyl terephthalaldehyde, 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine and nitrogen-vacancy-containing graphitic carbon nitride obtained in step S1 as raw materials, 1,2-dichlorobenzene and n-butanol as solvents, and acetic acid as catalyst, a solvothermal method was used to prepare a vinyl covalent organic framework combined with nitrogen-vacancy-containing graphitic carbon nitride composite material.

[0086] S3, Hydroxyl covalent organic framework material / nitrogen vacancy graphitic carbon nitride: Using 2,5-dihydroxyterephthalaldehyde, 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine and nitrogen-vacancy-containing graphitic carbon nitride obtained in step S1 as raw materials, 1,2-dichlorobenzene and n-butanol as solvents, and acetic acid as catalyst, a solvothermal method was used to prepare a hydroxy covalent organic framework combined with nitrogen-vacancy-containing graphitic carbon nitride composite material.

[0087] The specific process for preparing graphitic carbon nitride containing nitrogen vacancies in step S1 is as follows: A mixture of melamine (15g) and potassium hydroxide (0.5g) is added to a sample boat in a tube furnace. The tube furnace is then closed, and nitrogen gas is introduced into the furnace at a rate of 20mL / min. After 30min, the tube furnace is heated to 550℃ and maintained for 4h at a heating rate of 10℃ / min. The resulting pale yellow solid is ground into powder using an agate mortar and pestle.

[0088] The preparation method of vinyl covalent organic framework material / nitrogen vacancy graphitic carbon nitride includes the following steps: A mixture of nitrogen vacancy-containing graphitic carbon nitride (80 mg), 2,5-divinyl terephthalaldehyde (40 mg), and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine (55 mg) prepared in step S1 is added to a high-temperature resistant glass tube (outer diameter 9.8 mm, inner diameter 6 mm). Then, 1,2-dichlorobenzene (1 mL), n-butanol (1 mL), and acetic acid (0.2 mL, 6 mol·L⁻¹) are added. -1 After stirring and ultrasonic dispersion for 20 min, the mixture was frozen in liquid nitrogen, evacuated for 2 min, and thawed at room temperature. The freezing-vacuum-thawing process was repeated three times. Finally, the heat-resistant glass tube was sealed with a flame at 1300℃ and stored in an oven at 120℃ for 3 days. After cooling to room temperature, the solid precipitate was collected by centrifugation and washed several times with anhydrous N,N-dimethylacetamide and tetrahydrofuran until the supernatant became colorless. The covalent organic framework of the product was washed with acetone and dried under vacuum to obtain a vinyl covalent organic framework combined with graphitic carbon nitride containing nitrogen vacancies.

[0089] The preparation method of hydroxyl covalent organic framework material / nitrogen vacancy graphitic carbon nitride includes the following steps: A mixture of nitrogen vacancy-containing graphitic carbon nitride (80 mg), 2,5-dihydroxyterephthalaldehyde (40 mg), and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine (55 mg) prepared in step S1 is added to a high-temperature resistant glass tube (outer diameter 9.8 mm, inner diameter 6 mm). Then, 1,2-dichlorobenzene (1 mL), n-butanol (1 mL), and acetic acid (0.2 mL, 6 mol·L⁻¹) are added. -1 After stirring and ultrasonic dispersion for 20 min, the mixture was frozen in liquid nitrogen, vacuumed for 2 min, and then thawed at room temperature. This freezing-vacuum-thawing process was repeated three times. Finally, the heat-resistant glass tube was sealed with a flame at 1300℃ and stored in an oven at 120℃ for 3 days. After cooling to room temperature, the solid precipitate was collected by centrifugation and washed several times with anhydrous N,N-dimethylacetamide and tetrahydrofuran until the supernatant became colorless. The covalent organic framework of the product was washed with acetone and dried under vacuum to obtain a hydroxyl covalent organic framework combined with a graphitic carbon nitride composite containing nitrogen vacancies.

[0090] A method for analyzing chlorophenolic compounds in water using vinyl or hydroxyl covalent organic framework materials / nitrogen-vacancy graphitic carbon nitride comprises the following steps: Vinyl covalent organic framework material / nitrogen-vacancy graphitic carbon nitride or hydroxyl covalent organic framework material / nitrogen-vacancy graphitic carbon nitride is added to a 100 mL double-layer quartz reactor, followed by the addition of water or an aqueous solution containing chlorophenols. Under dark conditions, the material is uniformly dispersed in the solution by magnetic stirring for 30 min to achieve adsorption-desorption equilibrium of the chlorophenols. After the reaction is complete, the material is separated from the liquid using a high-speed centrifuge (9000 rpm, 8 min). The chlorophenols adsorbed on the surface of the material are eluted and concentrated using acetonitrile to obtain the test sample solution. The test sample solution is analyzed using gas chromatography with an electron capture detector. Positive samples, i.e., samples containing chlorophenolic compounds, are retested using gas chromatography-tandem triple quadrupole mass spectrometry.

[0091] The above method for analyzing chlorophenolic compounds in water includes one or more of 4-chlorophenol, 2,4-dichlorophenol, and 2,4,6-trichlorophenol.

[0092] The above method for analyzing chlorophenol compounds in water includes one or more of the following water samples: surface water, groundwater, tap water, or filtered domestic sewage.

[0093] A method for removing chlorophenol compounds from water using vinyl or hydroxyl covalent organic framework materials / nitrogen-vacancy graphitic carbon nitride comprises the following steps: Vinyl covalent organic framework material / nitrogen-vacancy graphitic carbon nitride or hydroxyl covalent organic framework material / nitrogen-vacancy graphitic carbon nitride is added to a 100 mL double-layer quartz reactor, followed by the addition of an aqueous solution containing chlorophenols; under dark conditions, the material is uniformly dispersed in the solution by magnetic stirring for 30 min to achieve adsorption-desorption equilibrium of the chlorophenols. The suspension is then irradiated with visible light, and a condenser is turned on during this period to maintain the reactor temperature at 23–25 °C. After the reaction was complete, the material was separated from the liquid using a high-speed centrifuge (9000 rpm, 8 min). Acetonitrile was used to elute and concentrate the chlorophenols adsorbed on the surface of the material. Liquid-liquid extraction was used to enrich the residual chlorophenols in the solution. Gas chromatography with an electron capture detector was used to quantify the concentration of chlorophenol compounds in the eluent and extract. The degradation efficiency of the two covalent organic framework materials / nitrogen-vacancy graphitic carbon nitride on chlorophenol compounds was calculated.

[0094] The above-described method utilizes vinyl or hydroxyl covalent organic framework materials / nitrogen-vacancy graphite phase carbon nitride for the analysis and removal of chlorophenolic compounds in water. The chlorophenolic compounds are one or a mixture of several of 4-chlorophenol, 2,4-dichlorophenol, and 2,4,6-trichlorophenol, with a concentration of 1–2 mg / L. The mass ratio of the vinyl covalent organic framework material / nitrogen-vacancy graphite phase carbon nitride or the hydroxyl covalent organic framework material / nitrogen-vacancy graphite phase carbon nitride to the volume of the chlorophenol solution is 1 g: 2.5 L. The visible light irradiation time is 200–300 min.

[0095] Example 1: Preparation of vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 composite materials

[0096] Specifically, the steps include the following:

[0097] S1. Preparation of g-C3N4 material containing nitrogen vacancies: A mixture of melamine (15g) and potassium hydroxide (0.5g) was added to a sample boat in a tube furnace. The tube furnace was then closed, and nitrogen gas was introduced into the furnace at a rate of 20mL / min. After 30min, the tube furnace was heated to 550℃ and maintained for 4h at a heating rate of 10℃ / min. The resulting pale yellow solid was ground into powder using an agate mortar and pestle, which is the g-C3N4 material containing nitrogen vacancies.

[0098] S2. Preparation of vinyl COFs / nitrogen-vacancy g-C3N4 composite material: The mixture of g-C3N4 containing nitrogen vacancies (80 mg), 2,5-divinyl terephthalaldehyde (40 mg), and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine (55 mg) prepared in step S1 was added to a high-temperature resistant glass tube (outer diameter 9.8 mm, inner diameter 6 mm), followed by the addition of 1,2-dichlorobenzene (1 mL), n-butanol (1 mL), and acetic acid (0.2 mL, 6 mol·L⁻¹). -1 After ultrasonic dispersion for 20–25 min (frequency 80 kHz), the mixture was frozen in liquid nitrogen for 2–3 min, evacuated for 2–3 min, and thawed at room temperature for 2–3 min. This freezing-vacuum-thawing process was repeated three times. Finally, the heat-resistant glass tube was sealed with a flame at 1300 °C and stored in an oven at 120 °C for 3 days. After cooling to room temperature, the solid precipitate was collected by high-speed centrifugation (9000 rpm, 8–10 min) and washed 5–8 times with anhydrous N,N-dimethylacetamide and tetrahydrofuran until the supernatant became colorless. The covalent organic framework of the product was washed with acetone and dried under vacuum overnight (50 Pa, 60 °C) to obtain the vinyl COFs / nitrogen vacancy g-C3N4 composite material.

[0099] S3. Preparation of hydroxyl COFs / nitrogen vacancy g-C3N4 composite material: The mixture of g-C3N4 containing nitrogen vacancies (80 mg), 2,5-dihydroxyterephthalaldehyde (40 mg), and 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine (55 mg) prepared in step S1 was added to a high-temperature resistant glass tube (outer diameter 9.8 mm, inner diameter 6 mm), and then 1,2-dichlorobenzene (1 mL), n-butanol (1 mL), and acetic acid (0.2 mL, 6 mol·L⁻¹) were added. -1 After ultrasonic dispersion for 20–25 min (frequency 80 kHz), the mixture was frozen in liquid nitrogen for 2–3 min, evacuated for 2–3 min, and thawed at room temperature for 2–3 min. This freezing-vacuum-thawing process was repeated three times. Finally, the heat-resistant glass tube was sealed with a flame at 1300 °C and stored in an oven at 120 °C for 3 days. After cooling to room temperature, the solid precipitate was collected by high-speed centrifugation (9000 rpm, 8–10 min) and washed 5–8 times with anhydrous N,N-dimethylacetamide and tetrahydrofuran until the supernatant became colorless. The covalent organic framework of the product was washed with acetone and dried under vacuum overnight (50 Pa, 60 °C) to obtain a hydroxyl covalent organic framework combined with a graphitic carbon nitride composite containing nitrogen vacancies.

[0100] A schematic diagram of the transmission electron microscopy characterization of the vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 composite material prepared in Example 1 is shown below. Figure 1 As shown. By Figure 1 It can be seen that the synthesized materials have clear morphologies and exhibit a hexagonal symmetrical lattice. The diameter of the hydroxyl COFs / nitrogen vacancy g-C3N4 composite material is approximately 150 nm, while the diameter of the vinyl COFs / nitrogen vacancy g-C3N4 composite material is smaller, approximately 50 nm.

[0101] Example 2: Analysis of Chlorophenolic Compounds in Water Using Vinyl or Hydroxyl COFs / Nitrogen Vacancy g-C3N4 Composites

[0102] The analysis of chlorophenol compounds in water includes the following steps:

[0103] (1) Preparation of the sample solution to be tested

[0104] a. Extraction: 50 mL of ambient water was added to a quartz reactor and mixed with 20 mg of vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 composite material. The mixture was then added to a rotor and placed on a magnetic stirrer, where it was stirred at 100 rpm for 30 min. After extraction, chlorophenolic compounds in the water were adsorbed onto the composite material.

[0105] b. Elution: The material was separated from the liquid using a high-speed centrifuge (9000 rpm, 8 min). 2 mL of acetonitrile was added and the mixture was sonicated for 2 min to elute the chlorophenol adsorbed on the surface of the composite material. The material was then separated from the liquid using centrifugal force, and the elution was repeated twice. The eluents were then combined.

[0106] c. Concentration: The collected eluent was dried under nitrogen at 45°C, and 1 mL of n-hexane was added to dissolve it again to obtain the sample solution to be tested.

[0107] (2) Plotting working curves using the external standard method

[0108] Take appropriate amounts of the chlorophenol mixed standard solution and place them in 25 mL volumetric flasks. Dilute stepwise with n-hexane to prepare a standard series with at least five concentration points. The mass concentrations of the chlorophenol compounds are 0.05 μg / mL, 0.1 μg / mL, 0.25 μg / mL, 0.5 μg / mL, and 1 μg / mL, respectively. Analyze the concentrations sequentially from low to high according to the instrument reference conditions. Plot a working curve with chlorophenol concentration on the x-axis and peak area on the y-axis.

[0109] (3) GC-ECD and GC-QQQ were used to analyze and detect the test sample solution.

[0110] The chlorophenols in the sample solution prepared in (1) were separated and detected using GC-ECD. The peak areas were then incorporated into the standard curve obtained in (2) to calculate the concentration of chlorophenols in the sample solution. The GC-ECD was performed using an Agilent 7890A gas chromatograph equipped with an autosampler. The column was an Agilent HP-5 capillary column (30m × 0.32mm, 0.25μm). High-purity nitrogen was used as the carrier gas at a flow rate of 1.0mL / min. The column oven was initially heated to 40℃ for 3min, then increased to 300℃ at a rate of 10℃ / min and held for 5min. The injection port temperature was 260℃; injection was performed in splitless mode; the injection volume was 1μL; the detector temperature was 300℃; and the make-up gas was nitrogen at a flow rate of 3.0mL / min.

[0111] For the positive samples containing chlorophenol compounds, the test sample solution was retested using GC-QQQ: The GC-QQQ instrument was an Agilent 7890A-7000B equipped with an autosampler; the column was an Agilent HP-5m capillary column (30m × 0.25mm, 0.25μm); high-purity helium was used as the carrier gas at a flow rate of 1.0mL / min; the column oven temperature was initially 40℃ and held for 3min, then increased to 300℃ at a rate of 10℃ / min and held for 5min; the injection port temperature was 260℃; the injection was performed in splitless mode; the injection volume was 1μL. Multiple reaction monitoring (MRM) was used for scanning, with retention time and two pairs of molecular ion / fragment ion pairs used for qualitative analysis (relevant parameters are shown in Table 1), and the peak area of ​​the molecular ion / fragment ion pair with the strongest response signal used for quantification. The total ion chromatogram of chlorophenol compounds is shown below. Figure 2 As shown, all three chlorophenol compounds exhibited good resolution and response signal values.

[0112] Table 1. Analytical parameters of GC-QQQ for chlorophenols

[0113]

[0114] Quantitative analysis of fragment ions

[0115] Example 3: Degradation of chlorophenols in water using vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 composite materials.

[0116] The photocatalytic degradation of chlorophenol compounds in water includes the following steps:

[0117] (1) Photocatalytic degradation

[0118] 20 mg of either vinyl COFs / nitrogen-vacancy g-C3N4 composite material or hydroxyl COFs / nitrogen-vacancy g-C3N4 composite material was added to a 100 mL double-layer quartz reactor, followed by 50 mL of an aqueous solution containing chlorophenol. Under dark conditions, the material was uniformly dispersed in the solution using magnetic stirring for 30 min to achieve adsorption-desorption equilibrium of the chlorophenol organic matter. The suspension was then placed in a 300 W visible light irradiation area for 200–300 min. During this period, the cooling water was turned on to maintain the reactor temperature at 23–25 °C.

[0119] (2) Undegraded chlorophenols in the enrichment system

[0120] The material was separated from the aqueous phase using a high-speed centrifuge (9000 rpm, 8 min).

[0121] 2 mL of acetonitrile was added to the separated catalyst, and the mixture was sonicated for 2 min to elute the trace analytes adsorbed on the surface of the composite material. The elution was repeated twice, followed by centrifugation. The eluents were collected and combined. The collected eluents were dried under nitrogen at 45 °C, and 1 mL of n-hexane was added to re-dissolve the eluents to obtain the sample solution. The chlorophenols in the sample solution were analyzed and quantified using GC-ECD to obtain the chlorophenol content in the sample solution.

[0122] Add 50 mL of acetonitrile to the aqueous phase from which the catalyst was separated, homogenize and shake for 2 min, add 10 g of sodium chloride, shake well to dissolve and reach equilibrium, allow to stand and separate into layers, and remove the organic phase; add 30 mL of acetonitrile again, repeat the extraction once, combine the organic phases, and dry the combined organic phases at 45 °C by nitrogen blowing or rotary evaporation, add 1 mL of n-hexane to re-dissolve, and obtain the extract. Analyze and quantify the chlorophenol compounds in the extract using GC-ECD to obtain the chlorophenol content in the extract.

[0123] (3) Calculate the degradation efficiency of the material for chlorophenols.

[0124] The chlorophenol contents in the sample solution and the aqueous extract were summed, and then divided by the initial content of chlorophenol compounds in the water to calculate the photocatalytic efficiency of vinyl or hydroxyl COFs / nitrogen vacancy g-C3N4 for chlorophenol compounds in the water. The results are as follows: Figure 3 As shown, the two composite materials prepared in this invention, vinyl COFs / nitrogen vacancy g-C3N4 and hydroxyl COFs / nitrogen vacancy g-C3N4, both exhibit good degradation ability for the three chlorophenol compounds in water.

[0125] This invention uses melamine as a precursor and potassium hydroxide as an etchant to prepare graphitic carbon nitride containing nitrogen vacancies through a one-step calcination method under a nitrogen atmosphere. Then, using an organic compound containing organic functional groups, 4,4',4”-(1,3,5-triazine-1,3,5-triyl)triphenylamine, and graphitic carbon nitride containing nitrogen vacancies as raw materials, 1,2-dichlorobenzene and n-butanol as solvents, and acetic acid as a catalyst, a solvothermal method is employed to prepare g-C3N4 material with organic functional groups (COFs) / nitrogen vacancies. This material can not only be used as a solid-phase extraction adsorbent for detecting chlorophenols in water, but also as a photocatalyst for the photocatalytic degradation of chlorophenols in water. This solves the technical problems of difficult adsorption and treatment of chlorophenols in water, as well as the high energy consumption, high recombination rate of photogenerated carriers, and low degradation efficiency of traditional photocatalysts.

[0126] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a g-C3N4 material with organic functional groups COFs / nitrogen vacancies, characterized in that, Includes the following steps: S1. Preparation of graphitic carbon nitride containing nitrogen vacancies: Melamine and etching agent are mixed and calcined under a nitrogen atmosphere to obtain graphitic carbon nitride containing nitrogen vacancies. S2. Preparation of organic functional group COFs / nitrogen vacancy graphitic carbon nitride: The graphitic carbon nitride containing nitrogen vacancies, organic compounds containing organic functional groups, and 4,4',4''-(1,3,5-triazine-1,3,5-triyl)triphenylamine were mixed, organic solvent and catalyst were added, and the mixture was ultrasonically dispersed. After freezing, vacuum and thawing were repeated 2 to 4 times. The mixture was sealed and stored. After cooling, the solid precipitate was centrifuged and washed with anhydrous N,N-dimethylacetamide and tetrahydrofuran until the supernatant was colorless. Then it was washed with acetone and vacuum dried to obtain g-C3N4 material with organic functional group COFs / nitrogen vacancy. The mass ratio of the nitrogen-vacant graphitic carbon nitride, the organic compound containing an organic functional group, and 4,4',4''-(1,3,5-triazine-1,3,5-triyl)triphenylamine is (1.8~2.2):1:(1~1.5); the organic compound containing an organic functional group is 2,5-divinyl terephthalaldehyde or 2,5-dihydroxy terephthalaldehyde. In step S1, the etching agent is potassium hydroxide, and the mass ratio of melamine to potassium hydroxide is (20~40):1; In step S2, the organic solvent is one or more of 1,2-dichlorobenzene and n-butanol, and the mass-to-volume ratio of the nitrogen-vacant graphitic carbon nitride to the organic solvent is (30~50) mg:1 mL; the catalyst is an acetic acid solution, the mass-to-volume ratio of the nitrogen-vacant graphitic carbon nitride to the acetic acid solution is (380~420) mg:1 mL, and the concentration of the acetic acid solution is 6 mol·L⁻¹. -1 .

2. The preparation method according to claim 1, characterized in that, In step S1, the calcination conditions are as follows: heating to 400-600°C at a rate of 8-12°C / min for 3.5-4.5 hours.

3. The preparation method according to claim 1, characterized in that, In step S2, the ultrasonic dispersion conditions are: frequency 60~100Hz, time 20~25min; freezing conditions are: freezing in liquid nitrogen for 2~3min; vacuum conditions are: pressure not higher than 85Pa, time 2~3min; thawing conditions are: thawing at room temperature for 2~3min; the sealed storage time is 2~4 days, temperature is 100~120℃; centrifugation conditions are: speed 8000~10000rpm, time 8~10min.

4. A g-C3N4 material with organic functional groups COFs / nitrogen vacancies prepared by the preparation method according to any one of claims 1 to 3.

5. The application of a g-C3N4 material with organic functional group COFs / nitrogen vacancies prepared by the preparation method according to any one of claims 1 to 4, characterized in that, as follows: (1) Used for the detection of chlorophenol compounds in water; and / or (2) Used for photocatalytic degradation of chlorophenol compounds in water; The chlorophenolic compounds include one or more of 4-chlorophenol, 2,4-dichlorophenol, and 2,4,6-trichlorophenol.

6. The application according to claim 5, characterized in that, The method for detecting chlorophenol compounds in water samples includes the following steps: Sa1. Preparation of the sample solution to be tested: Using organic functional group COFs / nitrogen vacancy g-C3N4 as solid phase extraction adsorbent, chlorophenol compounds in water sample are extracted, organic functional group COFs / nitrogen vacancy g-C3N4 after extraction is eluted, and the eluent is concentrated to obtain the sample solution to be tested. Sa2. Detection of chlorophenolic compounds: The sample solution to be tested was separated and detected by GC-ECD, and a standard curve was plotted using the external standard method to calculate the concentration of chlorophenolic compounds in the sample solution. The GC-ECD was performed using an Agilent 7890A gas chromatograph equipped with an autosampler. The chromatographic column was an Agilent HP-5 capillary column, 30m × 0.32mm long and 0.25μm in diameter. High-purity nitrogen was used as the carrier gas at a flow rate of 1.0mL / min. The initial temperature of the column oven was 40℃ and held for 3min, followed by a temperature increase to 300℃ at a rate of 10℃ / min and held for 5min. The injection port temperature was 260℃. The split injection mode was 1:5, and the injection volume was 1μL.

7. The application according to claim 6, characterized in that, A method for photocatalytic degradation of chlorophenol compounds in water samples includes the following steps: adding an aqueous solution containing chlorophenol to g-C3N4 with organic functional groups COFs / nitrogen vacancies, stirring magnetically in the dark until the g-C3N4 with organic functional groups COFs / nitrogen vacancies is uniformly dispersed in the aqueous solution containing chlorophenol, obtaining a suspension, irradiating the suspension with visible light for 200-300 min at a temperature of 23-25℃, centrifuging to separate the liquid portion, and obtaining the water sample after degradation of chlorophenol compounds; wherein, the mass-to-volume ratio of the g-C3N4 with organic functional groups COFs / nitrogen vacancies to the aqueous solution containing chlorophenol compounds is 1 g:(2-3) L, and the concentration of chlorophenol compounds in the aqueous solution containing chlorophenol compounds is 1-2 mg / L; the magnetic stirring conditions are a rotation speed of 80-120 rpm and a time of 25-35 min; the centrifugation conditions are a rotation speed of 8000-10000 rpm and a time of 8-10 min.

8. The application according to any one of claims 6 or 7, characterized in that, The water sample includes one or more of the following: surface water, groundwater, tap water, or filtered domestic sewage.